2017
DOI: 10.1016/j.hpb.2017.02.199
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adjuvant chemotherapy on survival in patients with intrahepatic cholangiocarcinoma: a multi-institutional analysis

Abstract: done with resected specimens to examine the expression level of chemokine receptor CCR7 in cancer cells and elucidate whether the expression level is associated with lymph node metastasis. CCR7 staining was evaluated by visual assessment. Results: The membrane of distal bile duct cancer cells were heterogeneously immunostained by antibody for CCR7. 18 of 34 cases were positive for CCR7 expression (53%). 17 of 18 cases with lymph node metastasis were positive whereas 9 of 16 cases without lymph node metastasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…To this point, several studies have reported that liver‐directed therapy for recurrences, such as surgical resection, transarterial chemoembolization, and radiofrequency ablation, might improve the prognosis of patients with recurrent ICC . In addition, although the effect of adjuvant chemotherapy on the prognosis of ICC patients remains debatable, several studies have demonstrated potential survival benefits of adjuvant chemotherapy among “high‐risk” patients with advanced tumor characteristics, such as nodal metastasis, advanced stages, or an inadequate margin . As such, patients with MiVI should similarly be considered for appropriate adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…To this point, several studies have reported that liver‐directed therapy for recurrences, such as surgical resection, transarterial chemoembolization, and radiofrequency ablation, might improve the prognosis of patients with recurrent ICC . In addition, although the effect of adjuvant chemotherapy on the prognosis of ICC patients remains debatable, several studies have demonstrated potential survival benefits of adjuvant chemotherapy among “high‐risk” patients with advanced tumor characteristics, such as nodal metastasis, advanced stages, or an inadequate margin . As such, patients with MiVI should similarly be considered for appropriate adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Using a random-effect model, the pooled HR for the OS in the AT group was 0.60 (95%CI 0.51~0.69, Fig 6A), compared with the non-AT group. The effect of AT on the patients with LNM was evaluated in 4 included cohorts [9,16,24,26]. Using a random-effect model, the pooled HR for the OS in the AT group was 0.67 (95%CI 0.57~0.76, Fig 6B), compared with the non-AT group.…”
Section: Subgroup Analysis Stratified By High Risk Factorsmentioning
confidence: 99%
“…Various kinds of adjuvant therapies (AT), such as chemotherapy [8][9][10], radiotherapy [11,12], transarterial chemoembolization (TACE) [13,14], and chemoradiotherapy [15] have been conducted prevalently to improve the prognosis of patients after resection, and 21.4%-57.7% of patients were reported to receive AT after resection [14,16]. However, the benefit of AT remains controversial [8,9,12]. Considering that randomized controlled trials or prospective studies evaluating the clinical vale of AT are hard to conduct, a comprehensive systematic review and meta-analysis is needed to confirm it.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, AT, such as transarterial chemoembolization (TACE), chemotherapy, radiotherapy, and comprehensive treatment, has been conducted prevalently worldwide to improve ICC patient prognosis after radical resection . However, there is still controversy over whether ICC patients can benefit from AT after radical resection .…”
Section: Introductionmentioning
confidence: 99%